STRATEGI LEMBAGA PENDIDIKAN ISLAM DALAM MEMBANGUN BRANDING IMAGE - Akmal Mundiri (PEDAGOGIK : JURNAL PENDIDIKAN, 2016)
Efforts to develop the Islamic educational institutions is a necessity in the context of global economic developments which lately gave the signal the importance of increasing the independence and competitiveness of a coun- try in the international community, especially Indonesia will be confronted with the implementation of the ASEAN Economic Community (AEC). Ef- forts to reform the Islamic educational institutions can be done by improv- ing the quality of education. Similarly, the portrait on the challenges of educational institutions ahead with the competition so high that very many services offering of the educational institutions. The efforts of educational services marketing can be done with a good image branding strategy.In order to build relationships in the frame of branding image in the Is- lamic educational institutions is done by building brand awareness which is followed by building institutional perceived quality.